Indonesian BUILD OPERATES TRANSFER (BOT) performing in partnership - Mohammad Benny Alexandri, Neneng Siti Maryam, Heru Nurasa,; Sugandi, Yogi Suprayogi (Opción, 2020)
The purpose of this study is to find out the obstacles that arise during financing cooperation with the Cooperation through Build Operate Transfer (BOT) partnership model in the management of traditional government-owned markets via a qualitative descriptive study. The results of the study showed that the implementation of this collaboration is a mutually beneficial agreement. In conclusion, the agreement does not regulate much about third parties, namely traders, even though there should be adequate rights and obligations for traders.